Tingkat Pengetahuan Masyarakat Terdidik Dalam Mitigasi Bencana Longsor Lahan (Studi Pendekatan Fenomenologi di Desa Pundungrejo, Kecamatan Tawangsari, Kabupaten Sukoharjo) - Wijayanto, Muhammad, Dr. Tjipto Subadi, M.Si (2013)
This study aims to: 1) know the process a disaster mitigation efforts to reduce the risk a landslides disaster in the Pundungrejo Village, Tawangsari Subdistrict, Sukoharjo District, 2) the characteristics a educated society in this village, 3) the level knowledge a educated society in landslide disaster mitigation in this village. 4) the role a educated society in landslide disaster mitigation through the establishment a preparedness culture against general public in this village. This research approach is qualitative. This study design is phenomenological with the social definition paradigm. Informants of this study are people's who have been through formal education according to its competence. Methods of data collection through questionnaire, observation, and interviews with First Order Understanding techniques. Analysis using Second Order Understanding. The results of this study are: 1) the process a disaster mitigation efforts to reduce the risk a landslides disaster in the study area with approach top-down and bottom-up, but is still not optimal, 2) the characteristics a educated society in the study area is influenced by the thinking of the community, economic, and educational levels with an attitude of mutual cooperation and tolerance. 3) the level a knowledge educated society in landslide disaster mitigation is still incomplete. 4) educated society have a role in disaster mitigation through the establishment a preparedness culture against general public in this village.